The role of microRNAs in defining LSECs cellular identity and in regulating F8 gene expression - Jamil, Muhammad Ahmer; Al-Rifai, Rawya; Nuesgen, Nicole; Altmüller, Janine; Oldenburg, Johannes; El-Maarri, Osman (Frontiers in Genetics, 2024)
Coagulation Factor VIII (FVIII) plays a pivotal role in the coagulation cascade, and deficiencies in its levels, as seen in Hemophilia A, can lead to significant health implications. Liver sinusoidal endothelial cells (LSECs) are the main producers and contributors of FVIII in blood, a fact we have previously elucidated through mRNA expression profiling when comparing these cells to other endothelial cell types. Our current investigation focuses on small microRNAs, analyzing their distinct expression patterns across various endothelial cells and hepatocytes. The outcome of this exploration underscores the discernible microRNAs expression differences that set LSECs apart from both hepatocytes (193 microRNAs at p < 0.05) and other endothelial cells (72 microRNAs at p < 0.05). Notably, the 134 and 35 overexpressed microRNAs in LSECs compared to hepatocytes and other endothelial cells, respectively, shed light on the unique functions of LSECs in the liver. Our investigation identified a panel of 10 microRNAs (miR-429, miR-200b-3p, miR-200a-3p, miR-216b-5p, miR-1185-5p, miR-19b-3p, miR-192-5p, miR-122-5p, miR-30c-2-3p, and miR-30a-5p) that distinctly define LSEC identity. Furthermore, our scrutiny extended to microRNAs implicated in F8 regulation, revealing a subset (miR-122-5p, miR-214-3p, miR-204-3p, and miR-2682-5p) whose expression intricately correlates with F8 expression within LSECs. This microRNA cohort emerges as a crucial modulator of F8, both directly through suppression and indirect effects on established F8-related transcription factors. The above microRNAs emerged as potential targets for innovative therapies in Hemophilia A patients.